Distinção entre hematogônias e blastos em pacientes portadores de leucemia linfocítica aguda de células B - Wohlfahrt, Aline Bicca (2013)
Hematogones are B-lineage lymphoid precursors cells normally found in bone marrow. The B-cell Acute Lymphocytic Leukemia (B-ALL) is a lymphocytic precursors neoplasia with consequent accumulation of immature cells called lymphoblasts in bone marrow. The increase of hematogones after treatment for B-ALL or marrow transplantation may cause doubt to the prognosis due to morphological and immunophenotypic similarities between these normal and malignant precursors cells. The aim of this study was to differentiate subpopulations of hematogones and B lymphoblasts by immunophenotyping using flow cytometry, attempting to identify the hematological laboratory profile at diagnosis and the environmental factors that characterize patients with B-ALL. Group 1 consisted of healthy controls free of hematologic malignancy and group 2 consisted of pediatric patients recently diagnosed with B-ALL before the start of chemotherapy, both in bone marrow samples. Antibodies directed against CD45, CD10, CD19, CD34 and mIgM (membrane) were used, which enabled us to distinguish the degree of cell maturation. Despite of the morphological and immunophenotypic similarities, hematogones and B lymphoblasts were differentiated by flow cytometry through distribution and continuous expression of antibodies on the association of CD45 x CD10 and mIgM x CD34 in B population. This technique allowed a better characterization of hematogones in healthy patients, with a progressive maturational pattern within the same cell population, with immature, intermediate and mature cells. The B lymphoblasts exhibited an incomplete maturation spectrum represented by a single population with immaturity characteristics. Among leukemia patients evaluated, 100% were white, with a predominance of children under 10 years (73%) and female sex (64%). These patients had lower hemoglobin levels (91% of cases), platelets (82%) and leukocytes (45.45%), with elevated leukocyte count in 27.3% of subjects. Predominant signs and symptoms were pallor, weakness, petechiae or bruising presence and fever. The same proportion of leukemic patients resided in both rural and urban zones. Patients living in rural area had features that can justify the etiology of ALL, as the professional connection of their parents to contact with toxic products. Morphological revision combined with immunophenotyping has allowed the correct cell identification and distinction between phenotypic subpopulations of hematogones and B lymphoblasts, contributing to an accurate laboratorial prognostic. Due to number of patients with B-ALL of this study, further researches are suggested to correlate the exposure of parents and leukemia patients to potentially oncogenic environmental factors, with the objective of preventing this neoplasia.